THE EFFECT OF SERVICE QUALITY, PRODUCT QUALITY, LOCATION, AND BRAND IMAGE ON CUSTOMER SATISFACTION AT PT INDOSAT OOREDOO Tbk. BATAM REGIONAL - Rimayang Anggun Laras Prastianty Ramli; Dini Anggraini; Ervin Nora Susanti (BENING, 2022)
This study aims to determine the effect of service quality, product quality, location and brand image on consumer satisfaction. The population in this study are consumers of PT Indosat Ooredoo Tbk. Regional Batam in April 2022 – June 2022 as many as 315. The sample in this study was determined using the Slovin formula with an error rate of 10%, namely 76 respondents who were selected using a non-probability sampling technique, namely the incidental sampling method. This type of research is a quantitative type using primary data collected by questionnaire technique. The analytical method used is multiple linear regression which is processed using the SPSS 26 application. The results of the study state that service quality, product quality, location and brand image partially and simultaneously have a positive and significant effect on consumer satisfaction at PT Indosat Ooredoo Tbk. Batam Region.